Puss in Boots - "Perrault, Charles" (MM publications, 2008)
Puss in Boots is a European fairy tale that tells the story of a clever and resourceful cat who helps his poor master achieve wealth and nobility through cunning tricks and deception. Charles Perrault first popularized the tale in his 1697 collection Histoires ou contes du temps passé (Tales of Times Past), though earlier versions existed in Italian and other European traditions. The cat s wit and strategic use of disguise highlight themes of social mobility, intelligence, and fortune.
Keywords: folktale